Detection of mainland Kedah’s shoreline changes (2013-2020); a case study - Wan-Afnizan, W M; Al-Qadami, E H H; Razi, M A M; Aminon, N A; Aziz, A (2023)
Shoreline erosion and accretion are natural processes that involve the gradual change in the shape and position of coastlines due to the movement of water, sediment, and geological factors. These processes have significant implications for coastal environments, ecosystems, and human activities. Therefore, it is essential to frequently assess the shoreline changes for effective coastal management, sustainable development, and safeguarding valuable ecosystems. In the present study, shoreline condition along mainland Kedah (109 km) was investigated through remote sensing and geographical information system (GIS) techniques. The assessment was performed over the period of 7 years (2013 and 2020) by analysing the satellite images captured by Landsat-8 satellite Operational Land Imager (OLI) at 15 m resolution. Preprocessing was established by performing image geometric correction and registration. Next, the Support Vector Machines (SVMs) toolbox was used for image classification to define the water and non-water fields. Later, the shoreline was extracted from the classified images and overlaid in a geodetic base in ArcGIS software to detect shoreline changes. The results showed that the majority of mainland Kedah’s shoreline did not experience extensive erosion or accretion at which 54% of the shoreline (58.8 km) was found to be stable. Erosion was observed at 6 locations with a total length of 10.1 km (9% of the total shoreline length) which was mainly concentrated in the nonprotected areas. On the other hand, shoreline accretion was observed at 19 locations with a total length of 40.1 km (37% of the total length). It is worth highlighting that the erosion areas were concentrated in the southern part of the coastline, while the accretion areas were distributed between the middle part and the north side of mainland Kedah’s shoreline